2020
DOI: 10.3390/ani10020326
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Glutamine Metabolism and Its Role in Immunity, a Comprehensive Review

Abstract: In the body of an animal, glutamine is a plentiful and very useful amino acid. Glutamine consumption in the body of animals in normal or disease conditions is the same or higher than the glucose. Many in vivo as well as in vitro experiments have been conducted to evaluate the importance of glutamine. Glutamine is a valuable nutrient for the proliferation of the lymphocytes. It also plays a crucial role in the production of cytokines, macrophages, phagocytic, and neutrophil to kill the bacteria. Most of the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 80 publications
(107 reference statements)
0
34
0
Order By: Relevance
“…The concentration of this metabolite in the thyroiditis was similar as in the lesions. The immune cells utilize glutamine at high rates under the metabolic stress conditions 47 . Thus, the increased glutamate level in the thyroiditis as compared to goiter may be related to the enhanced conversion of glutamate from glutamine.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of this metabolite in the thyroiditis was similar as in the lesions. The immune cells utilize glutamine at high rates under the metabolic stress conditions 47 . Thus, the increased glutamate level in the thyroiditis as compared to goiter may be related to the enhanced conversion of glutamate from glutamine.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, activated B and T cells have an increased demand for glutamine for the production of IFN-γ and IL-2 and T cell proliferation [ 99 , 124 ]. Recent data showed that glutamine supplementation and metabolism is a vital part of the immune function and greatly reduces the risk of infectious complications in critically ill or surgical patients [ 125 , 126 ]. Oats, including all oat products listed in Table 1 , contain proteins at 12–13% dry weight, equivalents to at least 5.0 g protein per 40-g serving and provision of 8.9% of daily protein requirement of 0.8 g/kg body weight for a 70-kg American male adult ( Table 1 and Table 2 ).…”
Section: Proteins and Glutaminementioning
confidence: 99%
“…Glutamine is another element necessary for cellular proliferation and differentiation [ 116 ], and can promote proliferation in cancer cells [ 117 , 118 ]. Glutaminase (GLS) and glutamine synthetase (GS) are the two major enzymes involved in glutamine metabolism.…”
Section: Cancer Nichesmentioning
confidence: 99%